2020
DOI: 10.21203/rs.3.rs-34766/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hygiene along the continuum of care in the early post-natal period: an observational study in Nigeria

Abstract: Background Newborns delivered in healthcare facilities in low- and middle-income countries are at an increased risk of healthcare associated infections. Facility–based studies have focused primarily on healthcare worker behaviour during labour & delivery with limited attention to hygiene practices in post-natal care areas and largely ignore the wide variety of actors involved in maternal and neonatal care. Methods This exploratory mixed-methods study took place in six healthcare facilities in Nigeria whe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…One facility from each setting was assigned to receive the intervention. The referral hospital with the Hand hygiene compliance of birth attendants and caregivers along this care continuum remains low (13)(14)(15)(16). A recent systematic review of facility-based birth attendants' hand hygiene compliance in LMIC estimated compliance ranging from 1-38% (13).…”
Section: Study Setting and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…One facility from each setting was assigned to receive the intervention. The referral hospital with the Hand hygiene compliance of birth attendants and caregivers along this care continuum remains low (13)(14)(15)(16). A recent systematic review of facility-based birth attendants' hand hygiene compliance in LMIC estimated compliance ranging from 1-38% (13).…”
Section: Study Setting and Participantsmentioning
confidence: 99%
“…A recent systematic review of facility-based birth attendants' hand hygiene compliance in LMIC estimated compliance ranging from 1-38% (13). Observational studies of facility-based births in LMIC have identi ed multiple risks of infection to mothers and newborns due to inadequate hand hygiene practices during post-natal care in the facility through to the return to the household (14)(15)(16)(17)(18)(19).…”
Section: Study Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies of facility-based births in LMIC have identified multiple risks of infection to mothers and newborns due to inadequate hand hygiene practices during post-natal care in the facility through to the return to the household 14 19 . While global estimates are not available, both qualitative and quantitative studies suggest that hand hygiene compliance specific to newborn care is very low in low-resource settings—as low as 1% in Nigeria among healthcare workers and family members and 2.3–9.1% among mothers in Bangladesh 15 , 20 – 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Postnatal care in the critical days following facility-based birth remains under investigated 11 , 12 . The role and engagement of paternal and non-parental caregivers in LMIC in the provision of care across both environments has been documented 8 , 15 , 19 , 20 , 29 , 30 , however hand hygiene improvement strategies commonly only target birth attendants and mothers’ practices, leaving other important caregiver groups’ practices unaddressed 24 . There is a need for contextualised hand hygiene strategies that can span both the HCF and the home and effectively target hand hygiene practices of the multiple caregivers that lie along this pathway.…”
Section: Introductionmentioning
confidence: 99%